Analisis Faktor yang Mempengaruhi Akuntabilitas Pengelolaan Badan Usaha Milik Desa Dimoderasi Oleh Peran Kepala Desa - Anowta, Muhammad Ulvi (E-Jurnal Akuntansi; Vol 33 No 12 (2023), 2023)
The research aims to analyze the influence of management competency, community participation, use of information technology, on the management of Bumdes and find out whether management competency, community participation, use of information technology are moderated by the role of the village head on the accountability of Bumdes management. The population in this study were all BUMDes in West Sumbawa Regency using the Stratified Random Sampling method which was grouped into developing, active, growing strata with a total of 21 BUMDes. Determination of the sample consisting of administrators from BUMDes, namely the chairman, secretary and treasurer with the total sample in this study being 36 people representing 23 percent of the population. The data analysis tool used is SPSS 17. The research results show that management competency does not have a significant effect on the accountability of BUMDes management. Community participation and the use of information technology have a positive and significant effect on the accountability of BUMDes management. The role of the village head does not strengthen the influence of management competence on the accountability of BUMDes management, but the role of the village head is able to moderate the influence of community participation and the influence of information technology on the accountability of BUMDes management. Keywords :  Accountability of BUMDes Management